2020
DOI: 10.1007/s11804-020-00160-4
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Analysis of the Hydrodynamic Performance of a Three-Dimensional Finite-Length Rotating Cylinder

Abstract: The hydrodynamic performance of a three-dimensional finite-length rotating cylinder is studied by means of a physical tank and numerical simulation. First, according to the identified influencing factors, a hydrodynamic performance test of the rotating cylinder was carried out in a circulating water tank. In order to explore the changing law of hydrodynamic performance with these factors, a particle image velocimetry device was used to monitor the flow field. Subsequently, a computational field dynamics numeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The presented model tests did not allow for the measurement of the lift force generated by RC in operational conditions. However, the steady course keeping trial allowed to verify the empirical formula proposed for the isolated RC (Equation 3) [ 19 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presented model tests did not allow for the measurement of the lift force generated by RC in operational conditions. However, the steady course keeping trial allowed to verify the empirical formula proposed for the isolated RC (Equation 3) [ 19 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both the lift forces generated by RC and rudder can be estimated using lift force coefficients. The lift coefficient of the RC was obtained experimentally in [ 19 , 21 ], the lift coefficient of the rudder was the coefficient of the rudder profile of NACA (National Advisory Committee for Aeronautics) airfoil series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… The presented experimental test setup was constructed to observe all phenomena including vibrations without causing damage to the drive, supporting structure, and measuring devices. Wang et al [ 14 ] observed the vortex-induced vibrations increasing with the increase of the cylinder aspect ratio at the same value of α. The smooth progress of the experiment was affected for α of about 4 with a possible damage of devices.…”
Section: Discussionmentioning
confidence: 99%
“…In the experiment presented by Wang et al [ 14 ], the tested cylinder was installed under the plate situated on the water surface, eliminating the free surface effect and tip vortices on the top of the cylinder. For the cylinder of 0.1 m diameter and aspect ratio 1, at Reynolds numbers in the range of from Re = 2 × 10 5 to 1 × 10 6 and α = 2, the lift coefficient was equal to 3.5.…”
Section: Introductionmentioning
confidence: 99%